The Effect of pH on Adsorption Capacity Based on the Ionic Imprinted Polymer-Cd(II) Method - Nur Anisa Pungkasari; Maria Monica Sianita (Study Program of Chemistry, Faculty of Mathematics and Natural Sciences, Universitas Pakuan, 2025)
Population growth and technological advancement in Indonesia have contributed to increasing environmental pollution, particularly from industrial waste containing heavy metals such as cadmium (Cd²⁺). This pollution poses serious health risks as cadmium can enter the food chain through aquatic ecosystems. Therefore, effective separation methods are required to remove cadmium from water bodies. One such method is the use of Ionic Imprinted Polymer (IIP), which offers high selectivity toward specific metal ions. This study aimed to determine the adsorption capacity of cadmium using the IIP method, synthesized via precipitation polymerization, over pH values ranging from 3 to 8. CdCl₂ was used as the ion template, combined with Na₂EDTA as a chelating ligand, methacrylic acid (MAA) as the functional monomer, ethylene glycol dimethacrylate (EGDMA) as the crosslinker, and benzoyl peroxide (BPO) as the initiator. Characterization was conducted using Fourier Transform Infrared Spectroscopy (FTIR) to identify the functional groups and confirm template removal, and Scanning Electron Microscopy (SEM) to observe surface morphology. Adsorption performance was tested using Atomic Absorption Spectrophotometry (AAS). The IIP showed a specific absorption at 520 cm⁻¹ (Cd–O stretch), confirming the presence of cadmium-binding sites, and exhibited a porous morphology, unlike the dense structure of the blank polymer. The results showed that the optimum adsorption of Cd²⁺ occurred at pH 6, with an adsorption capacity of 4.47 mg/g, which was higher than that of the non-imprinted polymer (3.08 mg/g at pH 4). The improved adsorption performance at pH 6 is attributed to the predominance of the deprotonated EDTA form (Y⁴⁻), which forms a stable complex with Cd²⁺ (Kf ≈ 10¹⁶.⁵), thereby enhancing selective adsorption. These findings confirm that IIP-Cd is an effective material for cadmium removal from aqueous environments, with pH playing a critical role in optimizing adsorption capacity.